Can tropical grasses grown as cover crops improve soil phosphorus availability?. (21st September 2018) - Almeida, D. S.; Menezes‐Blackburn, D.; Rocha, K. F.; de Souza, M.; Zhang, H.; Haygarth, P. M.; Rosolem, C. A.
Abstract: Tropical grasses grown as cover crops can mobilize phosphorus (P) in soil and have been suggested as a tool to increase soil P cycling and bioavailability. The objective of this study was to evaluate the effect of tropical grasses on soil P dynamics, lability, desorption kinetics and bioavailability to soya bean, specifically to test the hypothesis that introducing grass species in the cropping system may affect soil P availability and soya bean development according to soil P concentration. Three grass species, ruzi grass ( Urochloa ruziziensis ), palisade grass ( Urochloa brizantha ) and Guinea grass ( Megathyrsus maximus ), were grown in soils with contrasting P status. Soya bean was grown after grasses to assess soil P bioavailability. Hedley P fractionation, microbial biomass P, phytase‐labile P and the diffusive gradient in thin films were determined, before and after cultivation. It was found that grasses remobilized soil P, reducing the concentration of recalcitrant P forms. The effect of grasses on changing the P desorption kinetics parameters did not directly explain the observed variation on P bioavailability to soya bean. Grasses and microorganisms solubilize recalcitrant organic P (Po ) forms and tropical grasses grown as cover crops increased P bioavailability to soya bean mainly due to the supply of P by decomposition of grass residues in low‐P soil. However, no clear advantages in soya bean P nutrition were observed when in rotation with these grasses in high‐P soil. This study indicates that further advantages in soya bean P nutrition after tropical grasses may be impeded by phytate, which is not readily available to plants.